2018
DOI: 10.1111/papr.12746
|View full text |Cite
|
Sign up to set email alerts
|

The Role of Sleep Quality and Fatigue on the Benefits of an Interdisciplinary Treatment for Adults With Chronic Pain

Abstract: Background Interdisciplinary chronic pain treatment is effective for reducing pain intensity and pain‐related disability, and for improving psychological function. However, the mechanisms that underlie these treatment‐related benefits are not yet well understood. Sleep problems and fatigue are modifiable factors often comorbid with chronic pain. The goal of this study was to evaluate the role that changes in sleep quality and fatigue might have on the benefits of an interdisciplinary chronic pain treatment. Me… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
21
0
1

Year Published

2019
2019
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 17 publications
(24 citation statements)
references
References 36 publications
2
21
0
1
Order By: Relevance
“…These results are consistent with those of a study of Swedish adolescents, which reported an association between short sleep duration and increased odds of pain problems [38]. Other studies have also demonstrated a link between poor sleep quality and increased pain during adolescence [39,40]. Disturbed sleep may affect the lives of adolescents in various ways and may manifest as issues associated with schoolrelated problems, poor concentration, and social problems [16].…”
Section: Discussionsupporting
confidence: 89%
“…These results are consistent with those of a study of Swedish adolescents, which reported an association between short sleep duration and increased odds of pain problems [38]. Other studies have also demonstrated a link between poor sleep quality and increased pain during adolescence [39,40]. Disturbed sleep may affect the lives of adolescents in various ways and may manifest as issues associated with schoolrelated problems, poor concentration, and social problems [16].…”
Section: Discussionsupporting
confidence: 89%
“…Although sleep and pain are temporally related, sleep quality appears to have a more robust influence on pain symptomatology than vice versa (Finan et al, 2013; Gerhart et al, 2017), and may even serve as a risk factor for pain development and chronification (Gupta et al, 2007; Finan et al, 2013). Likewise, intervening on sleep may have salutary effects on pain, with recent evidence highlighting the influence that treatment-related sleep improvements have on pain intensity (de la Vega et al, 2019). Exercise as a therapeutic modality also confers many health benefits but can be especially potent for pain symptomatology.…”
Section: Introductionmentioning
confidence: 99%
“…The current study was not designed to address the mechanism for the above mentioned correlation, although this may be explained by current literature. Pain is a well described modulator of sleep quality in chronic illness, with bi-directional relationship through which poor sleep increases pain perception and severe pain impairs sleep [37,38]. Specifically in CF, both children and adults, report higher prevalence of chronic pain and perceive the disease as being painful [39].…”
Section: Discussionmentioning
confidence: 99%